Pengaruh Pendidikan Kewirausahaan, Latar Belakang Keluarga, dan Jenis Kelamin terhadap Minat Berwirausaha Mahasiswa Fakultas Ekonomi Universitas Negeri Medan - Made Emi Sundari; Irsad Lubis (Attractive : Innovative Education Journal, 2024)
This research aims to determine the influence of entrepreneurship education, family background, and gender on students interest in entrepreneurship at the Faculty of Economics, Medan State University. The population in this study were all students from the Unimed Faculty of Economics class of 2017, totaling 621 students. The sample in this study was 93 students taken using proportional random sampling technique. The dependent variable in this research is interest in entrepreneurship (Y), while the independent variables include entrepreneurship education (X1), family background (X2), and gender (X3). The data collection method uses a questionnaire. Data analysis techniques use multiple linear regression, F test, t test, and coefficient of determination (R-square). The results of this research show that there is a positive and significant influence of the variables of entrepreneurship education, family background, and gender on the entrepreneurial interest of Unimed Faculty of Economics students. Based on the results of the coefficient of determination test, the percentage of independent variables on the dependent variable, namely entrepreneurship education, family background and gender on interest in entrepreneurship, was 54.3%.